Sidekicked - Anderson, John David, 1975- (Walden Pond Press, an imprint of HarperCollinsPublishers, 2013)
"Drew Bean might be a part of a secret organization for the training of superhero sidekicks, but that doesn't mean that life is all leaping tall buildings in single bounds.Drew is possessed of super senses--his hearing, sight, taste, touch, and smell are the most powerful on the planet--making him literally the most sensitive kid in school. And then there's his best friend, Jenna--their friendship would be complicated enough if she weren't able to throw an eighteen-wheeler the length of a city block. Add in trying to keep his sidekick life a secret from everyone, including his parents, and the truth is clear: middle school is pretty much a drag regardless of whether you have superpowers. But this is all before a supervillain long thought dead returns to the city of Justica and Drew's two identities threaten to crash head-on into each other. Drew has always found it pretty easy to separate right from wrong, good from evil. It's what a superhero does. But what happens when that line starts to disappear? Fans of The Extraordinary Adventures of Ordinary Boy will love Sidekicked, John David Anderson's hilarious middle-grade superhero novel"--